Ontology of illusions and genesis of meaning - Taddio, Luca (Scenari, 2021)
This essay aims to tackle the meaning of the concept of illusions in relation to the following terms: “appearance” and “deception of the senses”. We intend to examine some cases of illusion in order to show how the idea of “deceiving of the senses” is already a judgment on an experience: the senses themselves do not deceive indeed. Deception implies an epistemological position regarding reality. The same can be said of the relationship between appearance and reality: the appearance of illusions, compared to reality, is an epistemological question - and not an ontological one. Illusions are part of the reality and hence they convey a sense of it.